FT-IR study of N2 adsorption on ZnO and HgO modified Na-Y zeolite adsorbents - Chieng, Y. Y.; Kamarudin, Khairul Sozana Nor; Hamdan, Halimaton; Mat, Hanapi (2005)
FT-IR was used to study in situ gas-zeolite surface interactions and adsorbed species formed on ZnO and HgO modified Na-Y zeolites under ambient temperature (298 K). A general correlation between the integrated absorption band areas and the positions of v(N-N) bands interacting with the active adsorption sites on modified Na-Y zeolites are discussed. Results clearly demonstrate that the FT-IR bands of N2 adsorbed on ZnO and HgO modified Na-Y zeolite was governed not only by the properties of adsorbate but also by the nature and strength of the active adsorption sites present on the zeolite surfaces. In general, blue-shifted v(N-N) bands are obtained relative to the gas-phase Raman frequency, which are due to the different adsorption behavior of these adsorbed molecules with end-on orientation on the active adsorption sites. In addition, the adsorbing molecules interact strongly with the surface at initial stage. The strength of these interactions will then decrease as adsorption active sites are fully occupied.